Civatte Bodies in Pediatric Esophageal Biopsies: Does Lichen Esophagitis Pattern Occur in Children?. (July 2022) - Saab-Chalhoub, Mario W.; Correa, Hernán; Anderson, Julia L.; Kovach, Alexandra E.; Salaria, Safia N.
Purpose and context: Civatte bodies (CB) are associated with cutaneous and mucosal lichen planus in adults. They are a distinct feature of Lichen Esophagitis Pattern, which is not well described in children. We characterized clinicopathologic associations of archival esophageal CB at our Children's Hospital to determine whether lichen planus or Lichen Esophagitis Pattern occurs in children. Method: Pathology records were queried for pediatric esophageal biopsy diagnoses containing "CB, " "apoptosis, "necrosis, " or "dyskeratosis." Cases with concurrent eosinophilic/acute esophagitis were excluded. H&E slides and clinical reports were reviewed. Key results: Biopsies with CB or similar were identified from 19 patients and had been termed "dyskeratotic cells" in 8 reports. Patients had variable age and presenting symptoms, male predominance (74%), and frequent clinical history of polypharmacy (47%), Crohn disease (42%), and/or celiac disease (21%). Civatte bodies were prominent in the distal esophagus (95%), as few isolated cells (63%), and with variable chronic inflammation (absent, pauci-inflammatory, and lichen planus-like in approximately one-third of cases each). Conclusions: We show that esophageal CB from pediatric patients are under-recognized and may have different features and implications compared to Lichen Esophagitis Pattern in adults. Recognition and documentation of pediatric esophageal CB is needed to understand their clinical significance.